Growth and eGFP Production of CHO-K1 Suspension Cells Cultivated From Single Cell to Laboratory Scale - Schmitz, Julian; Hertel, Oliver; Yermakov, Boris; Noll, Thomas; Grünberger, Alexander (Frontiers in Bioengineering and Biotechnology, 2021)
Scaling down bioproduction processes became a major driving force for more accelerated and efficient process development over the last decades. Especially expensive and time-consuming processes like the production of biopharmaceuticals with mammalian cell lines benefit clearly from miniaturization, due to higher parallelization and increased insights while at the same time decreasing experimental time and costs. Lately, novel microfluidic methods have been developed, especially microfluidic single-cell cultivation (MSCC) devices proofed to be valuable to miniaturize the cultivation of mammalian cells. So far growth characteristics of microfluidic cultivated cell lines were not systematically compared to larger cultivation scales, however validation of a miniaturization tool against initial cultivation scales is mandatory to proof its applicability for bioprocess development. Here, we systematically investigate growth, morphology, and eGFP-production of CHO-K1 cells in different cultivation scales ranging from microfluidic chip (230 nL), shake flask (125 mL), and lab-scale stirred tank bioreactor (2.0 L). Our study shows a high comparability regarding specific growth rates, cellular diameters, and eGFP production which proofs the feasibility of MSCC as miniaturized cultivation tool for mammalian cell culture. In addition, we demonstrate that MSCC allows insights into cellular heterogeneity and single-cell dynamics concerning growth and production behavior which, when occurring in bioproduction processes, might severely affect process robustness.